Age-Related Changes in Peripheral and Central Sensory Conduction Times Estimated by Short Latency Somatosensory Evoked Potentials - Yamanouchi, Hirosi; Toyokura, Yasuo; Kuzuhara, Shigeki; Kohara, Nobuo (Nihon Rōnen Igakkai zasshi, 1988)
We studied age-related changes in peripheral and central sensory conduction times, using short latency somatosensory evoked potensials in 50 healthy volunteers aged between 26 and 84 years. The subjects were divided into three groups according to their age; young group consisted of 17 subjects (26-36 years), middleaged group, of 12 subjects (40-58 years), and aged group, of 21 subjects (61-84 years). Somatosensory evoked potentials following stimulation of the median nerve were recorded from the electrodes on the neck (N13) and the scalp (N19). Those following stimulation of the posterior tibial nerve were recorded from the 12th thoracic spine (N20) and scalp (P40). Peripheral conduction times were estimated by N13 and N20, while central conduction times, by CCT1 (N19-N13) and CCT2 (P40-N20). N13, N19, N20 and P40 significantly prolonged as the heights of the subjects increased; whereas CCT1 and CCT2 were not correlated with the heights of the subjects. Thus N13, N19, N20 and P40 corrected for the standard height (160cm) were used in the present study. N13 and N20 increased with age. On the other hand, N19, CCT1, P40 and CCT2 remained unchanged between young and middle-aged groups, but increased significantly in the aged group, compared to those of the other two groups. These results indicate that the effect of aging on sensory conductions differ between the central and peripheral sensory systems.